PENGARUH PENERAPAN MODEL KOOPERATIF LEARNING TIPE LISTENING TEAM TERHADAP HASIL BELAJAR IPAS SISWA KELAS VI A SDN 005 SAMARINDA SEBERANG TAHUN PEMBELAJARAN 2024/2025 - Akbar, Muhammad; Yudo Dwiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of applying the Listening Team Cooperative Learning model on the science and social studies learning outcomes of sixth-grade students at SDN 005 Samarinda Seberang in the 2024/2025 academic year. The background of this study stems from the low achievement of student learning outcomes, where 75% have not met the Learning Objective Achievement Criteria. This condition is thought to be influnced by the dominance of convensional methods that do not actively involve students. The type of research used is an experiment with a Quasi-Experimental Approach and a Non-Equivalent Control Group Design. The research population consisted of all sixth-grade students, with a sample of 48 students divided into experimental and control classes. The research insturments include tests (10 multiple-choice questions and 10 essay questions) and non-tests in the form of observations and documention. Data analysis was performed thourgh normality and homogeneity test, Independent Sample T-tests, and N-Gain calculations. The result showed that there was a significant difference between the experimental and control classes with a Sig. (2-tailed) velue of 0.000 (<0.05). This proves that the use of the Listening Team Cooperative Learning model can be an alternative effective learning strategy to increase student activity, understanding and involvement in the learning process.